Sustainable Alkali-Activated Slag Binders Based on Alternative Activators Sourced From Mineral Wool and Glass Waste - Pavlin, Majda; König, Katja; König, Jakob; Javornik, Uroš; Ducman, Vilma (Frontiers in Materials, 2022)
In the present study, four different locally available waste glass materials (bottle glass-BG, glass wool-GW, stone wool-SW and cathode-ray tube glass-CRTG) were treated with hot concentrated potassium hydroxide (KOH) in order to obtain alternative alkali activators (AAAs). We evaluated the suitability of the solutions obtained for use as AAAs in the production of AAMs. AAMs were prepared using electric arc furnace slag and selected AAAs with a higher content of dissolved Si. We evaluated the performance of the AAMs in comparison to that of slags activated with KOH or potassium-silicate (K-silicate). The compressive strength of the AAMs prepared with KOH-based AAAs were high when Si and Al were simultaneously abundant in the AAA (9.47 MPa when using the activator sourced from the CRTG), and low with the addition of KOH alone (1.97 MPa). The AAM produced using commercial K-silicate yielded the highest compressive strength (27.7 MPa). The porosity of the KOH-based AAM was lowest when an alternative BG-based activator was used (24.1%), when it was similar to that of the AAM prepared with a K-silicate. The BG-based activator had the highest silicon content (33.1 g/L), and NMR revealed that Si was present in the form of Q0, Q1 and Q2. The concentrations of toxic trace elements in the AAAs used for alkali activation of the slag were also determined, and leaching experiments were performed on the AAMs to evaluate the immobilisation potential of alkali-activated slag. In the SW AAAs the results show acceptable concentrations of trace and major elements with respect to the regulations on waste disposal sites, while in the activators prepared from BG, CRTG and GW some elements exceeded the allowable limits (Pb, Ba, Sb and As).